GlobSed: Updated Total Sediment Thickness in the World's Oceans. (2nd April 2019) - Straume, E. O.; Gaina, C.; Medvedev, S.; Hochmuth, K.; Gohl, K.; Whittaker, J. M.; Abdul Fattah, R.; Doornenbal, J. C.; Hopper, J. R.
Abstract: We present GlobSed, a new global 5‐arc‐minute total sediment thickness grid for the world's oceans and marginal seas. GlobSed covers a larger area than previously published global grids and incorporates updates for the NE Atlantic, Arctic, Southern Ocean, and Mediterranean regions, which results in a 29.7% increase in estimated total oceanic sediment volume. We use this new global grid and a revised global oceanic lithospheric age grid to assess the relationship between the total sediment thickness and age of the underlying oceanic lithosphere and its latitude. An analytical approximation model is used to mathematically describe sedimentation trends in major oceanic basins and to allow paleobathymetric reconstructions at any given geological time. This study provides a much‐needed update of the sediment thickness distribution of the world oceans and delivers a model for sedimentation rates on oceanic crust through time that agrees well with selected drill data used for comparison. Plain Language Summary: We have constructed a new global ocean sediment thickness map, GlobSed, from previously published maps and new data compiled in this study. GlobSed is used together with a new map of lithospheric ages developed for this study to analyze how sediment thickness changes with respect to the age of the underlying oceanic crust and latitude. The results show a clear age‐latitude dependence where sediment thickness increases with age of the oceanic crust, toward high southern and northern latitudes and toward the equator. In addition, we calculate the total volume of sediments in the oceans, which shows an increase of 29.7%, compared to previously published global maps. Further, we develop a mathematical formula for sediment thickness as a function of age and latitude that describes the sediment thickness pattern in the oceans within reasonable error, and we suggest that this is a good approximation for estimating sediment thickness in oceanic basins through time. Key Points: We compile a new global total sediment thickness grid (GlobSed) Sediment thickness distribution correlates with both age and latitude of the oceanic lithosphere Our new compilation covers a larger area and thereby increases the total sediment volume in the oceans by ~29.7% compared to previous data sets